Gerenciamento da Terapia Medicamentosa na atenção primária do município de Belo Horizonte: Uma autoetnografia da transformação profissional - Daniela Álvares Machado Silva (2016)
Primary Health Care (PHC) is the central point in SUS (Unified Health System) for the construction of Health Care Networks, whose focus is multi-professional, in order to take care of patients with an increasingly chronic nature. The Family Health Support Team (FHST) constitutes itself in a specialized background for family health strategy (FHS), acting in the locus of the APS itself. The lack of clarity in the role of the traditional pharmacist in patients care makesthe accountability and understanding of their actual contribution as a health professional difficult, making them vulnerable within FHST's performance proposition. In this sense, there must be a systematization of the clinical practice of the pharmacists inserted in the FHST, in order to increase benefits and patients safety related to medication use and promote the integration of these professionals in multi-professional teams. The Comprehensive Medication Management Service (CMM) uses the theoretical framework of pharmaceutical care, guiding attitudes and values so that the pharmacist takes responsibility for pharmacotherapeutic needs of the patient, preventing, identifying and solving problems related to the use of medication, constituting a solution possible to systematize this practice. The present auto ethnographic study was used for a better understanding of the experience of being a CMM service provider in a PHC in the city of Belo Horizonte, Minas Gerais, Brazil. Participant observation techniques and field diary observations were used to describe and systematically analyze the experiences of the researcher in order to understand a cultural experience as a FHSTs pharmacist. Semi-structured interviews with other pharmacists who live similar experiences in the PHC were conducted. The analysis of these narratives and the interviews led to findings on the clinical performance of the PHC pharmacist, which were divided into two articles. The first one describes the transformation experience of the traditional pharmacist into a care-oriented pharmacist. This reflective practice promotes a profound change in the way the pharmacist identifies with "care" and the "patients", the main themes discussed in the article. The second article covers the identification of the elements that guide the CMM practice systematization in the researcher's work context. Throughout the results, the "Proposal of integration of a CMM service in the health units flows" was discussed, and the themes "Construction of a new professional identity in a multi-professional team" and "Incorporation of new activities in the workroutine" were identified as the most important elements for the systematization of the clinical practice in the presented context. The autoethnography enabled a reflection on the pharmacists practice, raising some means for the construction of professional autonomy through the care process. The methodology provided criticismfor the current practice of the researcher as a professional, inciting the understanding of the space of patients care which she can effectively be part of. It also provided adequate information to promote the change of professional attitude and enlightened reflections on the necessary changes in the daily life and in the collective framework for the integration of this service in the community through primary care. Moreover, it clarified that the practice transformation is only possible through change of attitude combined with an environment that fosters caring.